2006
DOI: 10.1111/j.1540-8183.2006.00105.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow‐Reversal Device for Cerebral Protection During Carotid Artery Stenting—Acute and Long‐Term Results

Abstract: The acute results indicate that proximal occlusion and flow reversal for cerebral protection during carotid stenting is a safe and effective method. The low restenosis and complication rate during long-term follow-up is in accordance with other series of carotid angioplasty and shows that the occlusion balloons do not cause any long-term side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Patient selection, operator skill, and device design all remain important in optimizing outcomes in high-risk populations, including the very elderly. Previous, smaller investigations of flow reversal yielded results similar to those in the EMPiRE study [25,26,28,29]. In the largest of these, Parodi et al [28] employed flow reversal and Wallstents (Boston Scientific) to treat carotid artery stenosis in 200 patients.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Patient selection, operator skill, and device design all remain important in optimizing outcomes in high-risk populations, including the very elderly. Previous, smaller investigations of flow reversal yielded results similar to those in the EMPiRE study [25,26,28,29]. In the largest of these, Parodi et al [28] employed flow reversal and Wallstents (Boston Scientific) to treat carotid artery stenosis in 200 patients.…”
Section: Discussionmentioning
confidence: 58%
“…Three patients (1.5%) had a stroke or died within 30 days of the procedure. In the 56-patient series of Rabe et al [29], the 30-day stroke and death rate was 1.8%. Grunwald et al [26] reported a nonrandomized comparison between outcomes in 36 patients in whom flow reversal was used during CAS and 54 who underwent unprotected CAS.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Some patients will not tolerate the temporary balloon occlusion, and the device is quite bulky, which can be cumbersome in some patients with tortuous anatomy. Two European series with a total of 86 patients found no major ISs or deaths at 30 days when the flow-reversal technique was employed for CAS (Adami et al 2002;Rabe et al 2006). This device is commercially available in Europe and limited to investigational use in the United States.…”
Section: Carotid Angioplasty and Stenting Early Randomized Control Trmentioning
confidence: 99%